359. Ventilator-associated pneumonia in patients with SARS-CoV-2–associated acute respiratory failure requiring mechanical ventilation: a retrospective cohort study. (31st December 2020) - Luyt, Charles-Edouard; Vidal, Pauline; Burrel, Sonia; Hekimian, Guillaume; Brechot, Nicolas; Schmidt, Matthieu; Combes, Alain; Boutolleau, David; Robert, Jérôme; Chastre, Jean
Abstract: Background: Data on incidence, clinical presentation and outcomes of ventilator-associated pneumonia (VAP) in patients with severe coronavirus disease 2019 (COVID-19) pneumonia requiring mechanical ventilation (MV) are limited. Methods: Case series of patients with COVID-19 pneumonia admitted to a single ICU in France. All consecutive patients requiring MV with RT-PCR–confirmed SARS-CoV-2 infection between March 12th and April 24 th, 2020 were included. Frequency, clinical characteristics, responsible pathogens and outcomes of VAP were assessed, and compared to an historical cohort of patients with severe influenza-associated pneumonia requiring MV admitted to the same ICU during the preceding three winter seasons. Results: Fifty-four consecutive patients with COVID-19–associated respiratory failure requiring MV were included (median (IQR) age 48 (42–58) years; 74% male; 93% requiring veno-venous ECMO). VAP occurred in 46 (85%) of them (median (IQR) prior MV duration before the first episode, 11 (8–16) days) (Table 1). Pathogens responsible for VAP were predominantly Enterobacteriaceae (72%), and particularly inducible AmpC-cephalosporinase producers (41%), followed by Pseudomonas aeruginosa (35%) (Table 2). Pulmonary infection recurrence and death were observed in 46 (85%) and 17 (31%) patients, respectively. Details on recurrent episodes and pathogens responsible for recurrences are given in Table 3. Most recurrences were relapse (i.e. infection with the same pathogen), with a high proportion occurring during antimicrobial treatment despite its adequacy. Despite a high rate of P. aeruginosa VAP in patients with influenza-associated ARDS, pulmonary infection recurrence rate was significantly lower than in patients with COVID-19. Overall mortality was similar in the two groups. Baseline characteristics of patients Characteristics of first ventilator-associated pneumonia episode Characteristics of recurrent VAP episodes in Covid-19 and influenza patients. Conclusion: Patients with severe COVID-19–associated respiratory failure requiring MV had a very high late-onset VAP rate. Inducible AmpC cephalosporinase–producing Enterobacteriaceae and Pseudomonas aeruginosa appeared to be frequently responsible for VAP, with multiple subsequent episodes and difficulties to eradicate the pathogen from the lung. Disclosures: All Authors : No reported disclosures